New issues in Islamic finance and economics : progress and challenges - Iqbal, Zamir; Iqbal, Zamir; Mirakhor, Abbas (Hoboken, N.J. : Wiley ; Chichester : John Wiley, 2009)
"The authors argue that the future success of Islamic finance will depend on a number of developments, including: economic and financial reform in Islamic countries, institutional reform and liberalization (leading to the development of transparent and efficient institutions), governance and regulatory oversight of Islamic financial institutions and products (affecting the reputation of Islamic institutions and products), research into the development of Shari'ah-compatible financial products, the pace of economic growth in Islamic countries (determining the demand for Shari'ah-compatible financial products), and on the direction and further developments in financial globalization."--BOOK JACKET.
Glossary of Arabic Terms -- 1. The Development and Progress of Islamic Finance -- 2. Issues and Challenges -- 3. Islamic Finance and Globalization: Convergence and a Boost for Rapid Growth? -- 4. Globalization and Its Implications for Muslim Countries -- 5. Expanding Financial Frontiers -- 6. Reputational Risk for the Islamic Financial Industry -- 7. The Design of Benchmarks for Asset Pricing -- 8. Qard-ul-Hassan-based Microfinance -- 9. Developing the Theoretical Foundations of Economics in Islam -- 10. Islam and Economic Development -- 11. Taxation and Public Expenditure in Islam -- 12. The Scope of the Social Safety Net in Islam: A Case Study.
includes index.
Keywords: Finance -- Islamic countries; Financial institutions -- Islamic countries